2014
DOI: 10.3390/ijms150711760
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Suppresses Chondrosarcoma Metastasis through Up-Regulation of miR-141 by Modulating PKCδ and c-Src Signaling Pathway

Abstract: Chondrosarcoma, a primary malignant bone cancer, has potential for local invasion and distant metastasis, especially to the lungs. Patients diagnosed with it show poor prognosis. Paeonol (2'-hydroxy-4'-methoxyacetophenone), the main active compound of traditional Chinese remedy Paeonia lactiflora Pallas, exhibits anti-inflammatory and anti-tumor activity; whether paeonol regulates metastatic chondrosarcoma is largely unknown. Here, we find paeonol do not increase apoptosis. By contrast, at non-cytotoxic concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Besides, Ying et al reported that PAE exercises its protective effects on renal injury in diabetic nephropathy rats (Y. Chen et al, ). In addition, accumulating evidence indicated that PAE upregulated several miRs, such as miR‐1 and miR‐142 (Horng et al, ; J. Wu et al, ), which is consistent with our result that PAE increased miR‐124 expression. Furthermore, our results showed that downregulated lncRNA HOTAIR inhibited RIF by downregulating Notch1 through upregulation of miR‐124.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, Ying et al reported that PAE exercises its protective effects on renal injury in diabetic nephropathy rats (Y. Chen et al, ). In addition, accumulating evidence indicated that PAE upregulated several miRs, such as miR‐1 and miR‐142 (Horng et al, ; J. Wu et al, ), which is consistent with our result that PAE increased miR‐124 expression. Furthermore, our results showed that downregulated lncRNA HOTAIR inhibited RIF by downregulating Notch1 through upregulation of miR‐124.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of Src on the metastasis of osteosarcoma cells is therefore controversial. A number of studies reported that inhibition of c-Src signaling was able to reduce metastasis of chondrosarcoma (57,58). Other studies found that Src inhibition could overcome chemoresistance to induce apoptosis and to inhibit migration (59).…”
Section: Src In Sarcoma Invasion and Metastasismentioning
confidence: 99%
“…Chondrosarcoma is one of malignant bone tumors and has a tendency of local invasion and distant metastasis [106]. A traditional Chinese remedy named Paeonol (2'-hydroxy-4'-methoxyacetophenone) was proved to be capable of inhibiting chondrosarcoma cell migration and invasion though upregulation of miR-141 via PKC and c-Src pathways [107].…”
Section: Mir-141 and Tumor Invasion And Metastasismentioning
confidence: 99%